Catalpol Alleviates Ang II-Induced Renal Injury Through NF‐κB Pathway and TGF-β1/Smads Pathway. Issue 1 (January 2022) - Cong, Cong; Yuan, Xiaohong; Hu, Ying; Chen, Wenjing; Wang, Yong; Tao, Lei
Abstract : Abstract: Catalpol is an iridoid glycoside obtained from Rehmannia glutinosa, which in previous studies showed various pharmacological properties, including anti-inflammatory, antioxidant, antidiabetic, antitumor, and dopaminergic neurons protecting effects. Here, we examined the effect of catalpol on renal injury induced by angiotensin II (Ang II) and further to explore its latent molecular mechanisms. We used an in vivo model of Ang II-induced renal injury mice; catalpol (25, 50, and 100 mg/kg) was administered for 28 days. Mouse glomerular mesangial cells (SV40 MES 13), rat kidney interstitial fibroblasts cells (NRK-49F), and human proximal tubular epithelial cells (HK-2) were induced by Ang II (10 µM) in the presence or absence of catalpol (1, 5, and 10 µM) and incubated for 48 hours in vitro. In our study, periodic acid-Schiff and Masson staining of renal tissue showed that catalpol reduced Ang II-induced renal injury in a concentration-dependent manner. The positive expressions of collagen IV and TGF-β1 were observed to decrease sharply after catalpol treatment. In renal tissue, the levels of pro-inflammatory cytokines tumor necrosis factor α and interleukin 6 were evidently decreased after catalpol intervention. Catalpol can relieve Ang II-induced renal injury by inactivating NF‐κB and TGF-β1/Smads signaling pathways. Therefore, catalpol may act as a potential drug to treat Ang II-induced renal injury.